How and when do purchasers successfully contribute to the implementation of circular purchasing: A comparative case-study. Issue 3 (June 2021) - Neessen, Petra C.M.; Caniëls, Marjolein C.J.; Vos, Bart; de Jong, Jeroen P.
Abstract: The transition towards a circular economy puts pressure on organizations to purchase in a circular manner. The aim of this research is to investigate the role, behaviors, and characteristics of purchasers in the circular purchasing process, and the contextual factors that influence circular purchasing. To address this aim, we interviewed purchasers, supervisors and policy makers of seven Dutch organizations. The results of the comparative case-study show that the main roles of the purchaser are those of coordinator, facilitator and advisor, and that the successful circular purchaser can best be described as intrapreneurial, sustainability-minded and knowledgeable about the circular economy. Purchasers are successful in implementing circular purchasing when they share responsibility with budget holders and when they are part of organizations that have processes in place to ensure the inclusion of circularity in their purchasing projects. The drivers that influence the success of circular purchasing can be described as creating a sense of direction and grasping the complexity of the circular economy. Furthermore, the market, organizational, legal, conceptual and cultural constraints that limit the success of circular purchasing were identified. Highlights: Circular purchasers are intrapreneurial, sustainability-minded and knowledgeable. Circular purchasers are successful when they share responsibility with budget holders. Circular purchasing drivers create a sense of direction and grasp complexity. Success limited by: market, organizational, legal, conceptual and cultural constraints.